Fostering employee engagement through human resource practices: a case of manufacturing firms in Malaysia - Johanim Johari; Zurina Adnan; Tan, Fee Yean; Khulida KiranaYahya; Site Nora Isa (Penerbit Universiti Kebangsaan Malaysia, 2013)
The primary objective of this study is to determine the influence of human resource management (HRM) practices on employee engagement. HRM practices comprise of training and development, financial and non-financial recognition, fringe benefits, and supervisor-subordinate relationship. A total of 306 operational level employees in manufacturing firms in the Northern Region of Peninsular Malaysia reported on HRM practices in their respective organizations as well as their level of engagement at work. Statistical analyses were conducted to examine the influence of HRM practices on employee engagement. The findings reported a significant and positive impact of financial and non-financial recognition as well as fringe benefits on employee engagement. The regression analysis result indicated that 40 percent of total variance of employee engagement was explained by HRM practices dimensions. Discussions elaborated on the research results while implications brought to fore the theoretical and practical contributions of this study. Finally, recommendations addressed several directions for future research.